Three Revolutions of the Modern Era - Richard A. Easterlin (Institute of Labor Economics (IZA), 2019)
The emergence and evolution of modern science since the 17th century has led to three major breakthroughs in the human condition. The first, the Industrial Revolution, started in the late 18th century and is based chiefly on developments associated with the rise of the natural sciences. The second, the Demographic Revolution, began in the latter half of the 19th century and is largely the result of progress in the life sciences. The third is a Happiness Revolution that commenced in the late 20th century and is the outgrowth of the social sciences. The first two revolutions, both familiar concepts, are summarized briefly; this paper develops the rationale for the third, the Happiness Revolution. It also notes the implications of this perspective for the interpretation of international cross-section studies.
Keywords: N30; I31; C21; 330; cross section; Scientific Revolution; Industrial Revolution; Demographic Revolution; happiness